The complete chloroplast genome of Swertia tetraptera and phylogenetic analysis - Yang, Lucun (Mitochondrial DNA B Resour, 2019)
Swertia tetraptera, native to the Qinghai-Tibetan Plateau, is an important traditional Chinese medicine. Although researchers have done a lot of work on it, the phylogenetic position of S. tetraptera within Swertia has still not been solved. Chloroplast genome sequences play a significant role in the development of molecular markers in plant phylogenetic and population genetic studies. In present study, we determined the complete chloroplast genome sequences for S. tetraptera using IIumina sequencing. The total length of the complete chloroplast genome of S. tetraptera is 152,840 bp, of which the GC content is 37.95%. The genome encodes 130 functional genes, including 85 protein-coding genes, 37 tRNA, and 8 rRNA. Phylogenetic analysis suggested that S. tetraptera forms monophyletic group with Halenia corniculata which shows closed relationship with the Halenia.